Hearing, seeing, and feeling speech: the neurophysiological correlates of trimodal speech perception - Hansmann, Doreen; Derrick, Donald; Theys, Catherine (Frontiers in Human Neuroscience, 2023)
To perceive speech, our brains process information from different sensory modalities. Previous electroencephalography (EEG) research has established that audio-visual information provides an advantage compared to auditory-only information during early auditory processing. In addition, behavioral research showed that auditory speech perception is not only enhanced by visual information but also by tactile information, transmitted by puffs of air arriving at the skin and aligned with speech. The current EEG study aimed to investigate whether the behavioral benefits of bimodal audio-aerotactile and trimodal audio-visual-aerotactile speech presentation are reflected in cortical auditory event-related neurophysiological responses. This is a provisional file, not the final typeset article To examine the influence of multimodal information on speech perception, 20 listeners conducted a two-alternative forced-choice syllable identification task at three different signal-to-noise levels.Behavioral results showed increased syllable identification accuracy when auditory information was complemented with visual information, but did not show the same effect for the addition of tactile information. Similarly, EEG results showed an amplitude suppression for the auditory N1 and P2 event-related potentials for the audio-visual and audio-visual-aerotactile modalities compared to auditory and audio-aerotactile presentations of the syllable /pa/. No statistically significant difference was present between audio-aerotactile and auditory-only modalities.Current findings are consistent with past EEG research showing a visually-induced amplitude suppression during early auditory processing. In addition, the significant neurophysiological effect of audio-visual but not audio-aerotactile presentation is in line with the large benefit of visual information but comparatively much smaller effect of aerotactile information on auditory speech perception previously identified in behavioral research.